2013
DOI: 10.1136/bmjqs-2012-001726
|View full text |Cite
|
Sign up to set email alerts
|

An intervention to improve transitions from NICU to ambulatory care: quasi-experimental study

Abstract: NCT01088945.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…6 Another trial that randomly assigned families to discharge preparation with a health coach before discharge but did not provide postdischarge follow-up showed no difference in health care utilization at 1 month after discharge. 46 Combined with our data, these results suggest that home visiting may be an effective peridischarge intervention, but interventions may be needed both before and after NICU discharge.…”
Section: Homementioning
confidence: 53%
“…6 Another trial that randomly assigned families to discharge preparation with a health coach before discharge but did not provide postdischarge follow-up showed no difference in health care utilization at 1 month after discharge. 46 Combined with our data, these results suggest that home visiting may be an effective peridischarge intervention, but interventions may be needed both before and after NICU discharge.…”
Section: Homementioning
confidence: 53%
“…** Both studies in which PCIs were evaluated (1 prepost study that was focused on children with multisystem complex illnesses and 1 prospective cohort study that was focused on the general population of children hospitalized) revealed an association with improved satisfaction. 43,86 CCIs were also associated with improved satisfaction across patient populations, including effective studies in children with chronic illnesses (n = 7), 43,44,48,49,52,53,64 patients in the NICU (n = 2), 78,80 and the general hospitalized population (n = 4). 86,87,89,94 CCIs that were associated with improved satisfaction included assistance with scheduling follow-up care, 43,53,89 in-home visits or follow-up telephone calls, 44,48,49,53,64,86,94 and intensive discharge planning.…”
Section: Results Of Individual Studies Regarding Patient And/or Caregmentioning
confidence: 99%
“…86,87,89,94 CCIs that were associated with improved satisfaction included assistance with scheduling follow-up care, 43,53,89 in-home visits or follow-up telephone calls, 44,48,49,53,64,86,94 and intensive discharge planning. 43,48,53,64,78,80,87,94 Similarly, FEIs were associated with improved satisfaction in children with chronic illnesses (n = 9), † † neonates (n = 3), 72,75,78 and general pediatric patients in the hospital (n = 4). 86,90,92,94 Effective FEIs included parental education (n = 13), ‡ ‡ written care plans for home (n = 1), 43 and cognitive behavioral therapy for parents (n = 1).…”
Section: Results Of Individual Studies Regarding Patient And/or Caregmentioning
confidence: 99%
“…2,3 Relatively little attention has been given to the impact and potential importance of this aspect of neonatal care, despite the huge volume of published literature on improving outcomes for preterm infants. 4 Improved education and information provided to families of preterm infants might improve the appropriate use of hospital and community health services after discharge, and reduce the numbers of babies readmitted to hospital, 5 although few studies have shown such a relationship.…”
Section: Chapter 2 Context and Backgroundmentioning
confidence: 99%
“…3 In the USA, the use of a health-coach programme to prepare families of infants with complex medical problems or born prematurely was explored. 5 The programme sought to help them to act as advocates for their infants. Families receiving health coaching were more likely to view the transition from hospital to home as positive within a few days of discharge, and to report confidence in knowing how to care for their baby.…”
Section: Mcgrathmentioning
confidence: 99%